A new look at the first dinosaur discovered in Antarctica: reappraisal of Antarctopelta oliveroi (Ankylosauria: Parankylosauria) - Soto Acuña, Sergio; Vargas, Alexander O.; Kaluza, Jonatan Ezequiel
The first dinosaur discovered in the Antarctic continent was the ankylosaur Antarctopelta oliveroi in the 1980s.Nevertheless, since then several hypotheses of phylogenetical relationships have been proposed because these have beendepended on how the skeletal remains have been interpreted. The main obstacle for clarifying its phylogenetic position is thatmany portions of the skeleton remain unknown, in addition to the presence of unknown characters in typical ankylosaurs.Considered an ankylosaurid, nodosaurid, or even a chimaera, a recent proposal based on mostly complete material of a newankylosaur from Chilean Patagonia provided support for a novel phylogenetic hypothesis: Antarctopelta and other southernankylosaurs are an early branching clade, the Parankylosauria, whose origin probably dates to the Late Jurassic. In the light ofthis new view, a redescription of the available skeletal remains is provided together with a new reconstruction of the firstAntarctic dinosaur known to the science community. Fil: Soto Acuña, Sergio. Universidad de Chile. Facultad de Ciencias Físicas y Matemáticas. Departamento de Geología; Chile Fil: Vargas, Alexander O. Universidad de Chile. Facultad de Ciencias Físicas y Matemáticas. Departamento de Geología; Chile Fil: Kaluza, Jonatan Ezequiel. Fundación de Historia Natural Félix de Azara; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina